2006
DOI: 10.1038/sj.jid.5700111
|View full text |Cite
|
Sign up to set email alerts
|

DHCR24 Gene Knockout Mice Demonstrate Lethal Dermopathy with Differentiation and Maturation Defects in the Epidermis

Abstract: Desmosterolosis is an autosomal recessive disorder due to mutations in the 3beta-hydroxysterol-Delta24 reductase (DHCR24) gene that encodes an enzyme catalyzing the conversion of desmosterol to cholesterol. To date, only two patients have been reported with severe developmental defects including craniofacial abnormalities and limb malformations. We employed mice with targeted disruption of DHCR24 to understand the pathophysiology of desmosterolosis. All DHCR24-/- mice died within a few hours after birth. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 49 publications
5
54
1
Order By: Relevance
“…These animals were around 25% smaller in size than DHCR24 C/C and DHCR24 C/K littermates at birth. In contrast to initial reports, it was subsequently demonstrated that these animals do not survive until adulthood: in fact, they show a lethal dermopathy at birth, associated with retention of epidermal water in agreement with similar observations in patients with desmosterolosis, and die within a few hours (Mirza et al 2006(Mirza et al , 2008.…”
Section: Seladin-1 As An Enzymecontrasting
confidence: 45%
“…These animals were around 25% smaller in size than DHCR24 C/C and DHCR24 C/K littermates at birth. In contrast to initial reports, it was subsequently demonstrated that these animals do not survive until adulthood: in fact, they show a lethal dermopathy at birth, associated with retention of epidermal water in agreement with similar observations in patients with desmosterolosis, and die within a few hours (Mirza et al 2006(Mirza et al , 2008.…”
Section: Seladin-1 As An Enzymecontrasting
confidence: 45%
“…Of note, mice with a deficiency of 3b-hydroxysterol-D24, the enzyme that catalyzes the conversion of desmosterol to cholesterol, have abundant desmosterol but no cholesterol in the epidermis. These animals die within a few hours after birth from an impaired cutaneous permeability, providing additional evidence for the importance of cholesterol for normal permeability barrier function (82). Together, these results demonstrate an important role for epidermal cholesterol synthesis in permeability barrier homeostasis.…”
Section: Jlr: What Regulates Lamellar Body Secretion?mentioning
confidence: 51%
“…Similar phenotypic alterations, such as malformation of the nervous system, have also been observed in other mutant mice with a defect in cholesterol biosynthesis (Liu et al 1999, Tozawa et al 1999, Fitzky et al 2001. Interestingly, the mutant mice deficient in Ebp, Sc5d, Dhcr24 and Dhcr7 survive until birth (Derry et al 1999, Fitzky et al 2001, Krakowiak et al 2003, Wechsler et al 2003, Mirza et al 2006, while the HSD17B7KO and mice deficient in the steps prior to the HSD17B7 (Liu et al 1999, Tozawa et al 1999, Caldas et al 2005) present with embryonic lethal phenotypes.…”
Section: Hsd17b7ko Mice As Shown Above In Addition Tomentioning
confidence: 53%